What an Important Implementation of the Educational Rights of Adopted Children in Indonesia from an Islamic Jurisprudence Perspective? - Meidina, Ahmad Rezy; Ali, Zezen Zainul; Puspita, Mega; Ashlakha, Hilma Nur; Zahro, Anisatuz (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
This research states that in Islamic law adopting a child is a good act, which helps adopted children get a proper education. Basically, implementing the above rights of children is an obligation and joint responsibility of the government and society. The phenomenon that occurs in Indonesia is that the educational rights of adopted children have shifted to utilization, due to several factors, one of which is economic. The aim of this research is to strengthen previous research, and examine further the shift in the educational rights of adopted children and look at the factors that result in non-fulfillment of adopted children’s rights in Indonesia. This research uses a normative sociological approach with the nature of the analytical descriptive research. The results of this research found several factors that resulted in shifting, even not being given the rights of adopted children.